Electroglottography in Dysphonics - Chandrashekar K.R (Journal of All India Institute of Speech and Hearing, 1970)
As majority of phonatory dysfunctions are associated with abnormal vibrations of the vocal cords, analysis of the vibration of the vocal cords in terms of differentparameters constitute an important aspect to be considered in the diagnosis and differential diagnosis of voice disorders.